METHODOLOGICAL BASIS FOR STUDYING THE INFLUENCE OF CORPORATE CULTURE ON ORGANIZATIONAL EFFECTIVENESS - Li Dong wei (Foundations and Trends in Research, 2024)
The article discusses the methodological foundations of the study of how corporate culture affects the effectiveness of an organization. The stages of the formation of corporate culture, important elements of its evolution and methods of assessing the level of culture within the organization are highlighted. During the research, the features of the development of corporate culture at different stages of the organization’s life cycle, as well as the role of managers in this process, were discussed. The main methods of creating a corporate culture, including deliberate and spontaneous formation based on the life cycle of the organization, were considered in the study of this topic. The advantages and disadvantages of corporate culture assessment methods, including the Denison questionnaire, OKAY and OCI, are considered. Additionally, the links between corporate culture and the achievement of strategic goals of the organization, employee engagement and the development of strong professional and interpersonal relationships are considered. As a conclusion, it should be noted the importance of corporate culture as a tool for improving the competitiveness and financial stability of an organization